System of Budget Planning, Programming, Development and Execution and the Defence Resources Management Model (DRMM) - Davor Čutić (Ekonomski Vjesnik, 2010)
The system of budget planning, programming, development and execution of the Ministry of Defence of the Republic of Croatia (henceforth: the Croatian acronym SPPIIP) is the basic system for the strategic management of defence resources through which an effective and rational distribution of available resources is conducted, based on the goals of national security of the Republic of Croatia. This system sets the principles of transparency and democratic management of defence resources while respecting the specificities of the defence system. The SPPIIP allows for decision making based on complete information about alternatives and the choice of the most economical and most efficient way to reach the goal. It unites the strategic plan, program and budget. It consists of four continuous, independent and interconnected phases: planning, programming, development and the execution of the budget. The processes of the phases are dynamic and cyclic. In addition to the SPPIIP, the Defence Resources Management Model (DRMM, Croatian acronym: MURO) has also been developed. This is an analytic tool which serves as a decision support system in the SPPIIP. The DRMM is a complex computer model showing graph and tabular overviews in a multi-year period. The model examines three areas: the strength of the forces, expenses and defence programs. The purpose of the model is cost and strength analysis and the analysis of compromise and feasibility, i.e. how sensitive the programs are to fiscal movements in the sphere of the MoD budget in the course of a multiyear cycle, until a certain project ends. The analysis results are an easily understandable basis for decision making. The SPPIIP and the DRMM are mutually independent systems, but they complement each other well. The SPPIIP uses the DRMM in designing and resource allocation based on the goals set. The quality of the DRMM depends on the amount and quality of data in its database. The DRMM can be used as a basis for independent decision making related to important strategic issues and is intended to provide answers to a series of questions from the areas of force structure, combat readiness, balance of powers and needs for personnel of a certain profile. Military analysts use DRMM results to explain key force structure issues to the decision makers. All the results of the model have to be analyzed in co-operation with military experts of a certain knowledge and capability profile, whilst constantly keeping the limitations of the model in mind.